Problem Dunia Ilmiah dan Krisis Spiritual - Hia, Hubertus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2018)
Spiritual awareness is one’s experience the living mind and body as a whole. It goes beyond mind and body, but also expands between the self and the world. At the center of human consciousness through the spiritual moments there is a sense of being deeply related with everything, the sense of being together with the whole universe. This kind of spiritual awareness has been threatened by the modern scientific world. The spirit of modernism to question and to break down nature, religion, and tradition under the pretext of pragmatic utopia of growth has brought humanity into an alarming and frightening phase of world civilization. Fritjof Capra says that the main problem of the existential crisis of modern humans is caused by the crisis of perception, mainly with the influence and errors from science as well as from Cartesian and Newtonian thoughts in perceiving the reality mechanically. Mysticism can be seen as an alternative to liberate modern humans to become authentic persons.